Training Pemeriksaan Payudara Sendiri (Sadari) Sebagai Upaya Deteksi Dini Kanker Payudara Di SMKN 3 Kota Bengkulu Tahun 2024 - Murwati, Murwati; Handayani, Tita Septi; Sulastri, Sulastri; Ningrum, Kartika Murya; Anabella, Tiara Syifa; Putri, Ena Purnama (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
In Indonesia, breast cancer attacks more women than men (KPKN, 2015), and around 70% of breast cancer patients come to the hospital in an advanced stage (Despitasari, 2017). The prognosis of breast cancer is closely related to the stage at which the cancer is diagnosed. An earlier diagnosis will help reduce mortality from breast cancer, therefore several screening and early diagnostic programs have been developed to detect breast cancer in the early stages (Rukmi, 2017). Breast self-examination (SADARI), clinical breast examination (CBE), and mammography are used as references for breast cancer screening (KPKN, 2015). One of the efforts that can be made in the context of early detection of breast cancer is breast self-examination (SADARI), which is an examination carried out by a person to detect breast conditions.